Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines on the Role of Surgery in the Management of Adults With Metastatic Brain Tumors. Issue 3 (9th January 2019) - Nahed, Brian V; Alvarez-Breckenridge, Christopher; Brastianos, Priscilla K; Shih, Helen; Sloan, Andrew; Ammirati, Mario; Kuo, John S; Ryken, Timothy C; Kalkanis, Steven N; Olson, Jeffrey J
Abstract: Please see the full-text version of this guideline https://www.cns.org/guidelines/guidelines-treatment-adults-metastatic-brain-tumors/chapter_2 ) for the target population of each recommendation listed below. SURGERY FOR METASTATIC BRAIN TUMORS AT NEW DIAGNOSIS QUESTION: Should patients with newly diagnosed metastatic brain tumors undergo surgery, stereotactic radiosurgery (SRS), or whole brain radiotherapy (WBRT)? RECOMMENDATIONS: Level 1: Surgery + WBRT is recommended as first-line treatment in patients with single brain metastases with favorable performance status and limited extracranial disease to extend overall survival, median survival, and local control. Level 3: Surgery plus SRS is recommended to provide survival benefit in patients with metastatic brain tumors Level 3: Multimodal treatments including either surgery + WBRT + SRS boost or surgery + WBRT are recommended as alternatives to WBRT + SRS in terms of providing overall survival and local control benefits. SURGERY AND RADIATION FOR METASTATIC BRAIN TUMORS QUESTION: Should patients with newly diagnosed metastatic brain tumors undergo surgical resection followed by WBRT, SRS, or another combination of these modalities? RECOMMENDATIONS: Level 1 : Surgery + WBRT is recommended as superior treatment to WBRT alone in patients with single brain metastases. Level 3 : Surgery + SRS is recommended as an alternative to treatment with SRS alone to benefit overall survival. Level 3 : It is recommended that SRS alone be considered equivalent to surgery + WBRT. SURGERY FOR RECURRENT METASTATIC BRAIN TUMORS QUESTION: Should patients with recurrent metastatic brain tumors undergo surgical resection? RECOMMENDATIONS: Level 3 : Craniotomy is recommended as a treatment for intracranial recurrence after initial surgery or SRS. SURGICAL TECHNIQUE AND RECURRENCE QUESTION A: Does the surgical technique (en bloc resection or piecemeal resection) affect recurrence? RECOMMENDATION: Level 3 : En bloc tumor resection, as opposed to piecemeal resection, is recommended to decrease the risk of postoperative leptomeningeal disease when resecting single brain metastases. QUESTION B: Does the extent of surgical resection (gross total resection or subtotal resection) affect recurrence? RECOMMENDATION: Level 3 : Gross total resection is recommended over subtotal resection in recursive partitioning analysis class I patients to improve overall survival and prolong time to recurrence. The full guideline can be found at https://www.cns.org/guidelines/guidelines-treatment-adults-metastatic-brain-tumors/chapter_2 .